Green dentistry: a systematic review for objective and subjective research - Saxena, Vrinda; Datla, Asmita; Deheriya, Manish (International Journal of Research in Medical Sciences, 2023)
Dentistry’s significant environmental impact and resource-intensive nature are concerning issues. Factors such as the environmental effects of biomaterials throughout lifecycle, radiation usage, and hazardous waste generation, including mercury and lead, need careful consideration. To counteract the environmental consequences of global warming, there is a growing global push to incorporate sustainability and green solutions. In response, dentists must transition from conventional practices to sustainable ones, embracing "green dentistry," which integrates sustainable development principles into dental care, underpinned by the 4 R’s: Reduce, Reuse, Rethink, and Recycle. To assess the knowledge, attitude, and practices of dental professionals towards green dentistry, a questionnaire-based study was conducted. The search for relevant literature encompassed terms like "green dentistry," "eco-friendly dentistry," "recycling dental waste," and "sustainability in dentistry" through PubMed from 2001 to 2023, including English-language scientific and grey literature. Analysis of dental professionals’ responses revealed notable disparities in eco-friendly dentistry knowledge between postgraduates (97.1%) and undergraduates (84.7%). Postgraduates exhibited better awareness of sterilization pouch disposal (68.1% vs. 49.2%) and mercury waste (85.5% vs. 61.9%). A substantial 82.9% recognized the potential for equipment recycling. While 16 articles were found from the PubMed database, spanning 2001 to 2023, originating from various sources, a broader exploration of quantitative and qualitative data on extraction was limited. There’s a dearth of national research trends in this field. The study participants displayed satisfactory awareness of eco-dentistry, along with reasonable attitudes and adoption rates. However, continuous high-quality research is essential to comprehensively understand the impacts of environmentally friendly dental practices.